2016
DOI: 10.1136/bmjqs-2016-005679
|View full text |Cite
|
Sign up to set email alerts
|

Variations in GPs' decisions to investigate suspected lung cancer: a factorial experiment using multimedia vignettes

Abstract: IntroductionLung cancer survival is low and comparatively poor in the UK. Patients with symptoms suggestive of lung cancer commonly consult primary care, but it is unclear how general practitioners (GPs) distinguish which patients require further investigation. This study examined how patients' clinical and sociodemographic characteristics influence GPs' decisions to initiate lung cancer investigations.MethodsA factorial experiment was conducted among a national sample of 227 English GPs using vignettes presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…The limited available information is only indirectly provided by a few interview studies and significant event audits. Studies examining cognitive processes, including vignette studies, may be particularly useful [135][136][137][138] .…”
Section: Research Prioritiesmentioning
confidence: 99%
“…The limited available information is only indirectly provided by a few interview studies and significant event audits. Studies examining cognitive processes, including vignette studies, may be particularly useful [135][136][137][138] .…”
Section: Research Prioritiesmentioning
confidence: 99%
“…This measure comprised indicators of three cognitive biases that eCREST sought to influence: the unpacking principle, confirmation bias and anchoring. These were identified by previous clinical reasoning research (29)(30)(31). The unpacking principle refers to the tendency to not elicit the necessary information to make an informed judgement.…”
Section: Clinical Reasoning Outcome Measuresmentioning
confidence: 99%
“…Controlled experiments using case vignettes or standardized patients can be conducted to demonstrate the occurrence of implicit bias in diagnostic decision-making. A vignette-based UK study involving general practitioners showed disparities for diagnostic evaluation for lung cancer [17]. The same vignette-based approach may hold promise in testing strategies that mitigate the occurrence of bias and subsequent disparities.…”
Section: Demographic Disparitiesmentioning
confidence: 99%